The spatio-temporal dynamics of the short-term rental market in Berlin (2008-2020) - The case of AirBnB - Pettas, Dimitris; Suwala, Lech (DIE ERDE – Journal of the Geographical Society of Berlin, 2023)
Over the last decade, the emergence and development of the digitally mediated short-term rental market (STR) has vastly disrupted urban housing and touristic accommodation markets. Whereas the fact about emergence and devel- opment of STR in cities is well-known, there are lesser insights on how this emergence and development takes place in space and time. In this short communication, we build on the case of Berlin – a city which has implemented a strict regulatory framework towards limiting housing misuse, including the provision of dwellings through short-term rental platforms – in order to explore the ways the short-term rental market emerged and expanded in the city. In doing so, we focus on both the spatial distribution of the listings and the quantitative attributes of the market, building on the analysis of data from the AirDNA dataset that contains all AirBnB listings (n = 104,746) in Berlin from 2008 to 2020. Our findings confirm the peak of spatial concentration of STR listings in predominantly central-city district tenement hous- ing quarters which, since the 1990’s, have gone through gentrification and touristification processes.